2021
DOI: 10.3390/pathogens10020244
|View full text |Cite
|
Sign up to set email alerts
|

Akt Interacts with Usutu Virus Polymerase, and Its Activity Modulates Viral Replication

Abstract: Usutu virus (USUV) is a flavivirus that mainly infects wild birds through the bite of Culex mosquitoes. Recent outbreaks have been associated with an increased number of cases in humans. Despite being a growing source of public health concerns, there is yet insufficient data on the virus or host cell targets for infection control. In this work we have investigated whether the cellular kinase Akt and USUV polymerase NS5 interact and co-localize in a cell. To this aim, we performed co-immunoprecipitation (Co-IP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…We confirmed that all these recombinant proteins were phosphorylated by Akt in vitro ( Figure 2 ). The phosphorylated positions of band-purified NS5s, including the corresponding to USUV previously described [ 11 ], were determined by mass spectrometry, with sequence coverage values of 93%, 95% and 96% for WNV, ZIKV and USUV NS5 proteins, respectively ( Supplementary Figure S1 ). The analysis revealed that the same residue, a Ser contained in the catalytic motif SGDD, was phosphorylated in all flaviviral NS5 proteins tested: S664, S669 and S670 in ZIKV, USUV, and WNV, respectively ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We confirmed that all these recombinant proteins were phosphorylated by Akt in vitro ( Figure 2 ). The phosphorylated positions of band-purified NS5s, including the corresponding to USUV previously described [ 11 ], were determined by mass spectrometry, with sequence coverage values of 93%, 95% and 96% for WNV, ZIKV and USUV NS5 proteins, respectively ( Supplementary Figure S1 ). The analysis revealed that the same residue, a Ser contained in the catalytic motif SGDD, was phosphorylated in all flaviviral NS5 proteins tested: S664, S669 and S670 in ZIKV, USUV, and WNV, respectively ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The expected sequence was confirmed by DNA sequencing for all the constructs. Plasmids encoding the entire NS5 protein and the RdRpD of USUV have been previously described [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations